Design thinking as an effective method for problem-setting and needfinding for entrepreneurial teams addressing wicked problems - Rahmin Bender-Salazar (Journal of Innovation and Entrepreneurship, 2023)
Organizations in a wide array of fields and disciplines are increasingly using design thinking as an innovative process to create products or services that address wicked problems in their industries. Design thinking, a method of creative and collaborative problem solving originating in the tactics of designers, is a product design and development process that is, more and more, being used as a tool to move innovation forward and structure creation processes in diverse disciplines, from product development to food creation to social science research. Increasingly design thinking has become popular beyond the confines of creative and design disciplines and into the realm of wicked problems in social and ecological systems. While design thinking has many forms and applications, this study uses a refined version built upon the key themes of inspiration, ideation, and implementation as defined by Tim Brown, CEO of IDEO (2009), and situates it within the social science discipline-namely, systems thinking, organizational learning, and action research. Through a distilled design structure this flexible methodology combines insights from organizational development, social psychology, systems theory, and design research. By embedding learning and reflective practices into the structure of design thinking, a hybrid model of design thinking emerges that is a more effective tool for framing, setting in context, and solving these types of problems within teams.
Keywords: 650; Design thinking; Design process; Needfinding; Organizational learning; Problem setting; Systems thinking; Wicked problems